(untitled) (World of finance, 2019)
Introduction. The general feature of the modern theory of globalization is the interdependence of economies of countries of the world, which is based on the transformation of national economics into an integrated global world economy. Permanent transformations of world economic processes lead to corresponding changes in the distribution and redistribution of capital. Essential growth of amounts and quantities of ІPO-transactions is showing the high efficiency of the principal financial instrument which is IPO-market. Purpose. The investigation of condition of transformation process on international capital market, installation of tendencies in changing of dynamic of the activity on world IPO market. Results. The globalization of financial markets has a revolutionary effect not only forworld financial market, but also for international investors and borrows of capital. The theoretical concept of globalization of financial markets provides of elimination barriers between domestic and international financial markets. The modern world economy is characterized by three tendencies such as new convergence, cyclical interdependence and dissimilarity in distribution. The essence and forms of manifestation ofthe financiaiization ofthe economics are deployed which leads to an increase in the financial depth of the economy. The essence of the international capital market is complemented by the analysis of problems ofthe development of IPO-market. Conclusion. The international capital market is in a condition of constant renewal through the positive influence of globalization processes in the world economy. The consolidation of Western stock exchanges on the IPO-market is continuing, while stock exchanges are expanding in developing countries throughjoint initiatives and closer integration.